2022
DOI: 10.1101/2022.08.25.505298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Presence of Myelinated Nerves and Schwann Cells in White Adipose Tissue: Proximity to Synaptic Vesicle Containing Nerve Terminals and Potential Role in BTBR ob/ob Demyelinating Diabetic Neuropathy

Abstract: Peripheral neuropathy is a pathophysiological state of nerve degeneration and loss of tissue innervation. The most prominent cause of small fiber neuropathy is diabetes which can be demyelinating in nature, but this has not yet been explored in adipose tissue. Both demyelinating neuropathies and axonopathies implicate Schwann cells (SCs), the peripheral glial required for nerve myelination and regeneration after injury. Here, we perform a comprehensive assessment of SCs and myelination patterns of subcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
3
1
Order By: Relevance
“…Fluorescence area of Z‐maximum intensity projections of the whole tissue was measured for nerve and blood vessels. We found that tissue innervation and vascularity somewhat increased with increased tissue mass (Figure S4 c), contrary to what was observed in the obese, diabetic, and neuropathic BTBR ob/ob mouse model (Wang et al, 2020 ; Willows, Gunsch, et al, 2022 ). Potentially, a relatively slow increase in fat mass (as with aging) allows the nerves and vasculature to respond adequately to tissue demands, in contrast to obese states.…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…Fluorescence area of Z‐maximum intensity projections of the whole tissue was measured for nerve and blood vessels. We found that tissue innervation and vascularity somewhat increased with increased tissue mass (Figure S4 c), contrary to what was observed in the obese, diabetic, and neuropathic BTBR ob/ob mouse model (Wang et al, 2020 ; Willows, Gunsch, et al, 2022 ). Potentially, a relatively slow increase in fat mass (as with aging) allows the nerves and vasculature to respond adequately to tissue demands, in contrast to obese states.…”
Section: Resultscontrasting
confidence: 86%
“…With our recent discovery of specialized synaptic vesicle‐containing nerve terminals in ing‐scWAT, the neuro‐adipose nexus (NAN) (Willows et al, 2021 ; Willows, Gunsch, et al, 2022 ), we concluded our analysis of adipose tissue innervation by assessing changes in NAN structure and/or number with age in 20‐, 60‐, and 100‐week‐old male HET3 mice. NANs were observed in all ing‐scWAT depots regardless of age; visualized by varicose axons clustering around specific adipocytes (visualized by their autofluorescence; Figure 6a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely, each tissue and organ in the body has unique structures to allow for specialized interoceptive stimuli, but the field is far from understanding these tissue and organ-specific specializations. Recent work deciphering the identity and diversity of nerve fiber subtypes in adipose tissues by us ( Willows et al, 2021 , Willows et al, 2022 ) and others ( Cao et al, 2018 , Zhang et al, 2018 ) has provided new evidence for the existence of nerves with myelination patterns and neuropeptide expression unique from those observed in the skin, as well as peptidergic sensory nerve subtype in adipose ( Willows et al, 2021 ). We have also identified the first nerve terminal structure in adipose, the neuro-adipose nexus (NAN) where nerve terminals containing synaptic markers and synaptic vesicles wrap around individual adipocytes on the surface of adipose depots ( Willows et al, 2021 ).…”
Section: Neuroanatomy Of the Sensory Nervous Systemmentioning
confidence: 99%